Leucine supplementation counteracts the atrophic effects of HDAC4 in rat skeletal muscle submitted to hindlimb immobilization - Alves, Paula; Cruz, André; Silva, William J.; Melazzo, Afonso M.; Labeit, Siegfried; Adams, Volker; Moriscot, Anselmo S. (Muscle & nerve, 2025)
Introduction/Aims We previously demonstrated that leucine supplementation significantly reduces histone deacetylase 4 (HDAC4) expression induced by hindlimb immobilization, thereby attenuating the increase in HDAC4 protein levels and nuclear accumulation. In this study, we investigated the impact of supraphysiological HDAC4 levels on skeletal muscle and the inhibitory potential of leucine in this scenario. Methods A total of 64 male Wistar rats were used in this study and subjected to electroporation of the soleus muscle with or without a plasmid overexpressing HDAC4 mRNA, followed by hindlimb immobilization and leucine supplementation (1.35 g/kg) for 7 days. Results Our findings revealed that HDAC4 overexpression alone led to soleus atrophy, resulting in a 23% decrease in mass, a 31% reduction in whole muscle cross-sectional area (CSA), and a 17% decrease in fiber CSA. These reductions were further exacerbated by hindlimb immobilization, with decreases of 50%, 46%, and 34%, respectively. Moreover, leucine supplementation protected against soleus atrophy and preserved soleus fiber CSA by 17%. This protective effect was accompanied by a 57% reduction in HDAC4-positive nuclear localization in immobilized rats overexpressing HDAC4. Discussion Our results indicate that HDAC4 forced expression can alone induce skeletal muscle atrophy. In addition, our results indicate that leucine is dominant in blocking HDAC4 signaling and highlight the use of this amino acid as a therapeutic tool in conditions involving skeletal muscle atrophy.
Erstmals veröffentlicht: 04. April 2025
Gesehen am 27.05.2025